2020
DOI: 10.1021/acsami.0c08683
|View full text |Cite
|
Sign up to set email alerts
|

Direct Printing of Asymmetric Electrodes for Improving Charge Injection/Extraction in Organic Electronics

Abstract: Engineering the energy levels of organic conducting materials can be useful for developing high-performance organic field-effect transistors (OFETs), whose electrodes must be well controlled to facilitate easy charge carrier transport from the source to drain through an active channel. However, symmetric source and drain electrodes that have the same energy levels are inevitably unfavorable for either charge injection or charge extraction. In this study, asymmetric source and drain electrodes are simply prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Remarkably, as shown in Figures c,d and S14, the PPy top-contacted DNTT transistor obtained a width-normalized contact resistance as small as 1.01 kΩ·cm under a −60 V gate voltage, which is much smaller than most of the conductive polymer contacted transistors with well-defined field-effect characteristics (Table ). ,, Although the contact resistance in this work is less than that of the reported device with conductive polymer electrodes, it should be noted that the lower contact resistance (tens and hundreds of Ω·cm) has been achieved with other combinations of organic semiconductor/ metal electrodes. , For the OFETs with top-contacted PPy electrodes, some reasons for the excellent contact performance can be understood as follows. (1) The PPy electrode film grown in situ is conformally adsorbed on the semiconductor, which effectively improves the quality of the interface between electrode and semiconductor.…”
Section: Resultsmentioning
confidence: 83%
“…Remarkably, as shown in Figures c,d and S14, the PPy top-contacted DNTT transistor obtained a width-normalized contact resistance as small as 1.01 kΩ·cm under a −60 V gate voltage, which is much smaller than most of the conductive polymer contacted transistors with well-defined field-effect characteristics (Table ). ,, Although the contact resistance in this work is less than that of the reported device with conductive polymer electrodes, it should be noted that the lower contact resistance (tens and hundreds of Ω·cm) has been achieved with other combinations of organic semiconductor/ metal electrodes. , For the OFETs with top-contacted PPy electrodes, some reasons for the excellent contact performance can be understood as follows. (1) The PPy electrode film grown in situ is conformally adsorbed on the semiconductor, which effectively improves the quality of the interface between electrode and semiconductor.…”
Section: Resultsmentioning
confidence: 83%
“…19,115 PEDOT:PSS, the most commonly used conductive polymer, is a water-soluble material that has been widely used as an electrode for OFETs by improving conductivity using eco-friendly solvents such as ethylene glycol and dimethyl sulfoxide. 116,117 Watersoluble and alcohol-based silver inks have also been widely utilized as electrode materials for OFETs. 118 Besides, Tang et al reported the MXene ink dissolved in ethanol, and applied the MXene source/drain electrodes for OFETs.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The high resolution is very important for the fabrication of the electronics with high density or precision as electrode, transistor, sensor, and heater. [11][12][13][14] Researchers have summarized the ink properties, the printer system, and the substrates for the e-jet printing. The mechanism of electrohydrodynamic-induced fluid movement, interface controlling, or e-jet printing as an additive manufacture method for flexible electronics has been reviewed.…”
Section: Fabrication Of Electronics By Electrohydrodynamic Jet Printingmentioning
confidence: 99%